Financial Literacy On Capital Aspect With Financial Inclusion As A Moderation Variable - Hanifah Indarwati; Sastiya Rahmawati; Veronica Wiratna Sujarweni (Islamic Accounting Journal, 2022)
This study aims to determine the effect of financial literacy on the aspects of capital with financial inclusion as a moderating variable in the Salatiga City MSMEs. This research was conducted at UMKM Salatiga City. The research sample was 105 respondents. This study uses a quantitative approach. The data collected from research is based on questionnaire distribution with a model of determining the sample using random sampling. The data analysis technique used is moderation regression analysis to test the hypothesis with the help of a computer SPSS program. Based on the results of this study, it shows that financial literacy has a positive and significant effect on the capital aspect. And the financial inclusion variable is able to strengthen the relationship between financial literacy and the capital aspects of MSMEs in the City of Salatiga.Keywords: Financial Literacy, Financial Inclusion, Capital Aspects